Formulation and quality evaluation of noodles with starchy flours containing high levels of resistant starch [pdf] - Beverly Cheruto Too; Ngo Van Tai; Nguyen Minh Thuy (My University, 2022)
Background.Increased consumption of foods high in resistant starch (RS) has been shown to prevent or manage type 2 diabetes, cardiovascular disease, and colon cancer.Materials and methods.The current study was carried out to identify the effects of supplementing noodles with high RS flour from red kidney beans, black turtle beans, mung beans, and potato starch on their RS content, quality properties, morphological appearance and consumer perception.The noodles were labelled F0 with 100% wheat flour, F1 with 22.5% high RS flour, F2 with 30% high RS flour, and F3 with 37.5% high RS flour.Results.The obtained results showed that the content of resistant starch in the noodles increased when some of the wheat flour was added/replaced with flour high in resistant starch content.The bright color of the noodles, L*, decreased significantly from the control sample F0 to the F3 formulation of noodles, which was attributed to the dark color of the supplemented flour, and the yellowness of the noodles also decreased.The addition of high RS flour had no significant effect on the hardness of the noodles.However, the cooking loss increased in the noodles from 6.09% in F0 to 9.87% in F3.The images from scanning electron microscopy showed increased pores in the noodles supplemented with high RS flour, which may explain the increased cooking loss.Consumers preferred the F2 noodles with 30% high RS flour supplementation.The incorporation of high RS flour into the noodle formulation increased RS content, but it had some negative effects on the quality parameters of the noodles. Conclusion.In order to achieve high RS noodles with acceptable quality, a suitable balance with the percentage of flour ought to be established when formulating products supplemented with high RS flour.
Keywords: Resistant Starch; Food composition and properties